2019
DOI: 10.1186/s40543-019-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Cr(VI) removal by bio-waste adsorbents: equilibrium, kinetics, and thermodynamic

Abstract: The green adsorbents were prepared by using cranberry (Cornus mas) kernel shell (CKS), rosehip (Rosa canina) seed shell (RSS), and banana (Musa cavendishii) peel (BP) and were proved in removing Cr(VI). Several parameters to remove Cr(VI) such as pH, adsorbent dosage, contact time, initial Cr(VI) ions concentration, and temperature were tested. The functional groups in the matrix of CKS, RSS, and BP were detected by FT-IR for raw biomasses together with Cr(VI). The equilibrium results were inspected using four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 28 publications
10
35
0
1
Order By: Relevance
“…Among all of the heavy metals, Cr is one of the main 16 toxic metals considered detrimental for human health [11]. Cr(III) is a human micronutrient, while Cr(VI) is extremely toxic and is a strong oxidizing agent [12]. The presence of Cr(VI) in water can cause severe diseases, such as kidney circulation, dermatitis and lung cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all of the heavy metals, Cr is one of the main 16 toxic metals considered detrimental for human health [11]. Cr(III) is a human micronutrient, while Cr(VI) is extremely toxic and is a strong oxidizing agent [12]. The presence of Cr(VI) in water can cause severe diseases, such as kidney circulation, dermatitis and lung cancer [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, strict environmental mechanisms and the enactment of legal standards is necessary to avoid excessive discharge of Cr(VI) into potable water sources [15]. The Environmental Protection Agency (EPA) has recommended that the maximum concentration of Cr(VI) in drinking water not exceed more than 0.05 mg/L [12].…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of chromium in the supply of waste are harmful to human health and environment (Parlayici and Pehlivan 2019). Many methods such as solvent extraction, filtration (Hanif and Shahzad 2014;Solomon et al 2013;Yang et al 2010), ion exchange, membrane process, precipitation, and adsorption were applied to Cr (VI) elimination from contaminated wastewater (Fan et al 2012;Kaya et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide annual production of dyes is about 7 × 10 5 tons and these dyes are discharged into waste streams by the aforementioned industries that cause negative impact to the environment and human health [1,2]. Besides from being highly coloured, studies have also shown that some dyes, dye precursors and their biotransformation products could be health threatening as they are toxic, mutagenic and carcinogenic in nature [3,4]. For instance, cationic dyes, which are widely used in colouring acrylic fibre are considered to be more toxic than other classes of dyes [5,6].…”
mentioning
confidence: 99%
“…Malachite Green (MG), which is a type of cationic dye, has been selected as the adsorbate in this study because from the available scientific evidence, MG poses a serious health concerning issue. MG is known to be a multi-organ toxin and its potential carcinogenic, teratogenic, mutagenic and genotoxic properties has been well documented [4,[7][8][9][10][11].…”
mentioning
confidence: 99%